Prove that (3-4sin^2A) (1-3Tan^2A)= (3-tan^2A) (4cos^2A-3)

8 answers

(3-4sin^2x) (1-3tan^2x)
= (3-4sin^2x) * (cos^2x-3sin^2x)/cos^2x
= (3-4sin^2x)/cos^2x * (cos^2x-3sin^2x)
= (3sec^2x-4tan^2x)(cos^2x-3sin^2x)
= (3+3tan^2x-4tan^2x)(cos^2x-3sin^2x)
= (3-tan^2x)(cos^2x-3sin^2x)

see if you can finish up from here
(3-4sin^2x) (1-3tan^2x)
= (3-4sin^2x) * (cos^2x-3sin^2x)/cos^2x
= (3-4sin^2x)/cos^2x * (cos^2x-3sin^2x)
= (3sec^2x-4tan^2x)(cos^2x-3sin^2x)
= (3+3tan^2x-4tan^2x)(cos^2x-3sin^2x)
= (3-tan^2x)(cos^2x-3sin^2x)
= (3-tan^2x)(cos^2x-3+3cos^2x)
= (3-tan^2x)(4cos^2x-3)
(3-4sin^2)(1-3tan^2)

(3-4sin^2)(1-3sin^/cos^2)
(3-4sin^2)(cos^2-3sin^2/cos^2)
(3-4sin^2/cos^2)(cos^2-3sin^2)
(3sec^2-4tan^2)(cos^2-3sin^2)
(3sec^2-4tan^2)(cos^2-3+3cos^2)
(3(1+tan^2-4tan^2)(4cos^2-3)
(3-tan^2)(4cos^2-3)proved
These answers were very helpfull thankyou
L.H.S= (3-4sin^2A)(1-3tan^2A)
(3-4sin^2A)(1-3sin^2/cos^2A)
(3-4sin^2A)(cos^2A-3sin^2A)/cos^2A
(3-4sin^2A)/cos^2A(cos^2A-3sin^2A)
(3sec^2A-4tan^2A)(cos^2A-3sin^2A)
(3sec^2A-4tan^2A)(cos^2A-3+3cos^2A)
(3+3tan^2A-4tan^2A)(4cos^2A-3)
(3-tan^2A)(4cos^2A-3)
R.H.S
Proved

Hope U like the answer...
Bshsvbb
Hh sin
Cos tan
Jonny
Miya
I'm sorry, but your response doesn't seem to make sense. If you have any questions or if there's anything specific you would like to discuss, please let me know and I'll be happy to help.
Fygyvyvg